2006
DOI: 10.1246/cl.2006.454
|View full text |Cite
|
Sign up to set email alerts
|

Localized Surface Plasmon Resonance Sensing Properties of Ag/TiO2 Films

Abstract: Ag nanoparticles were deposited on TiO2 films (Ag/TiO2 films) by photocatalytic means. When the film was immersed in various kinds of alcohols, the linear relationship was observed between the wavelength of localized surface plasmon resonance peak and the refractive index of the alcohols in the range of 1.33–1.41. The Ag/TiO2 films can be applied to the SPR sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…On the one hand, these samples have larger surface area‐to‐volume ratios, which lead to stronger photon absorption. On the other hand, it may be ascribed to the LSPR effect of spatially confined electrons in metallic Ag NPs . The higher absorption in the visible range may implicate higher activity in photocatalysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, these samples have larger surface area‐to‐volume ratios, which lead to stronger photon absorption. On the other hand, it may be ascribed to the LSPR effect of spatially confined electrons in metallic Ag NPs . The higher absorption in the visible range may implicate higher activity in photocatalysis.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it may be ascribed to the LSPR effect of spatially confined electrons in metallic Ag NPs. [37][38][39] The higher absorption in the visible range may implicate higher activity in photocatalysis. The visible-light photocatalytic property of the BFO bowl arrays and BFO bowl array coated with 10 nm Ag film, followed by annealing at 400°C for 20, 40, 60, and 80 min were evaluated by the degradation of RhB solution.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 A linear relationship was observed between the peak wavelength and the n 20 D of the alcohols in the range of 1.33 to 1.41. 6,7 It is also reported that the absorbance and peak wavelength of the LSPR absorption of metal nanoparticles are influenced by the size and shape of the metal particles themselves, the density of the particles, and the kinds of substrates on which they are deposited. 16 However, the effects of the number, size, and shape of the Ag nanoparticles on the sensitivity of the SPR sensors with the Ag/TiO 2 films have not been clarified.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10] Only a few papers reported the controllable formation of monodispersed metal nanoparticles by using the photoreduction method. 11 In our previous studies, 6,7 we have reported that the Ag/TiO 2 films showed the SPR sensing properties for the alcohols in the refractive index range of 1.33 to 1.41. However, the sensitivity of the SPR sensor using the Ag/TiO 2 films with different sizes and shapes of Ag nanoparticles has not been clarified.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation